New Directions in the History of the Jews in the Polish Lands. - Polonsky, Antony. (Jews of Poland Series, 2018)
Making use of the leading scholars in the field from Poland, Western Europe, North America and Israel, the volume provides a definitive overview of the history and culture of one of the most important communities in the long history of the Jewish people.